A erosão dos solos no contexto social - Guerra, Antonio José Teixeira (Anuário do Instituto de Geociências, 1994)
This paper aims to outline the need to include the social, economic and political issues on soil erosion studies. Therefore, the adoption of soil conservation strategies should take into consideration these issues. The paper also outlines the soil erosion problem, the political components of soil erosion, soil conservation policies, and finally shows why most soil conservation policies have failed, in developing countries, due to the traditional approaches used in most soil erosion and conservation programmes. Some alternative approaches are proposed, to deal with the problem, in order to reach sucess.